2018
DOI: 10.13005/bpj/1602
|View full text |Cite
|
Sign up to set email alerts
|

Study on Variations in the Origin and Branching Pattern of Internal Iliac Artery in Cadavers

Abstract: The variations in blood vessels are common and have long received the attention of anatomists and surgeons. The true pelvic cavity usually refers to that part of pelvis, which has its bony walls, the sacrum and lower part of hip bone. This small area is well covered by bones and has important structures namely the pelvic viscera, pelvic floor muscles, vessels and nerves supplying it. The aim of the study was to know the branching pattern of internal iliac artery based on the Adachis classification, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to Francis et al [34], the overall length of the right IIA equals 39.43 mm, and the left: is 36.10 mm. Furthermore, our research revealed that the overall diameter of the IIA is 6.86 mm.…”
Section: Discussionmentioning
confidence: 97%
“…According to Francis et al [34], the overall length of the right IIA equals 39.43 mm, and the left: is 36.10 mm. Furthermore, our research revealed that the overall diameter of the IIA is 6.86 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the length of the IIA is measured from the CIA bifurcation to the bifurcation into two terminal branches [19,20]. Other authors measured the length of the IIA from its origin to the point of bifurcation of the anterior and posterior divisions [21]. The length of the IIA varies among different populations [21].…”
Section: Length Of Iiamentioning
confidence: 99%
“…Other authors measured the length of the IIA from its origin to the point of bifurcation of the anterior and posterior divisions [21]. The length of the IIA varies among different populations [21]. Cadaveric studies have reported IIA lengths ranging from 0 to 90 mm (Table 1) [13,14,16,[18][19][20][21].…”
Section: Length Of Iiamentioning
confidence: 99%
See 2 more Smart Citations